(untitled) (International journal of artificial intelligence, 2024)
The rational nutrition of children of kindergarten age is of great importance in the growth and development of child oranism, in the adequate satisfaction of the demand for basic and complementary nutrients. The presence in the consumer food of growing organisms of macro-and micronutrients in the required amount ensures the normal course of physiological, biochemical processes in the body. The protection and strengthening of children's health has been and will remain the main task in any society. It is children who make up the most vulnerable and sensitive part of it and, at the same time, determine its future Labor, reproductive, intellectual and vital potential. There is a steady trend towards a 1.9-2.3-fold increase in obesity among children and adolescents, with the prevalence of digestive system diseases and nutrition-related diseases such as anemia.